ASSESSMENT OF SEMINAL TRAITS AND SUITABILITY OF SEMEN FOR CRYOPRESERVATION OF EXOTIC STALLIONS REARED UNDER INDIAN CONDITIONS - TALLURI, T R; RAVI, S K; LEGHA, R A; YASHPAL; THOMAS, T K; KASHYAP, S S; TRIPATHI, B N (The Indian Journal of Animal Reproduction, 2022)
Semen was collected from seven exotic stallions for the evaluation of seminal characteristics and freezabilityof semen. The appearance of fresh semen was milky-white to creamy and consistency of gel-free semen wasvariably thick. The total volume of semen, gel-free semen and gel in semen was 50.28±8.34, 43.57±8.14 and6.71±3.32 ml, respectively. The mass and progressive sperm motility in gel free semen was 88.71±1.70% and75.71±1.70%, respectively. Mean sperm concentration in fresh semen was 205.37±12.65 × 106 ml-1. The post-thawsperm motility was recorded up to an acceptable >30% (40.00±2.43%). The study indicated that the semen fromexotic stallions reared in India can be cryopreserved using conventional vapor freezing technique for encouragingartificial insemination and study of their fertility potential.
Keywords: Equine; Exotic stallion; HOST; Semen cryopreservation; Seminal parameters